The Role of Women in the Lebanese National and Political Movement (1943-1975)-A Historical Study - Sabah Algam Musa (Peerian Journals Publishing, 2025)
The period between 1943 and 1975 witnessed a progressive development in the role of women within the national and political movement in Lebanon. Women emerged as active elements in the struggle for independence, political participation, and the defense of social and economic rights. This was evident in women's participation in demonstrations against the French mandate and the demands for independence, the establishment of women's associations that supported national causes, and the struggle of women to obtain the right to vote (guaranteed since 1952) and to demand broader political rights. This research aims to shed light on the contributions of Lebanese women to the political and national movement during this period, in addition to analyzing the factors that developed or limited their participation
Keywords: Women's role; national movement; women's associations